Breast Milk Hormones and Regulation of Glucose Homeostasis - Francesco Savino; Stefania Alfonsina Liguori; Miriam Sorrenti; Maria Francesca Fissore; Roberto Oggero (Hindawi Limited, 2011)
Growing evidence suggests that a complex relationship exists between the central nervous system and peripheral organs involved in energy homeostasis. It consists in the balance between food intake and energy expenditure and includes the regulation of nutrient levels in storage organs, as well as in blood, in particular blood glucose. Therefore, food intake, energy expenditure, and glucose homeostasis are strictly connected to each other. Several hormones, such as leptin, adiponectin, resistin, and ghrelin, are involved in this complex regulation. These hormones play a role in the regulation of glucose metabolism and are involved in the development of obesity, diabetes, and metabolic syndrome. Recently, their presence in breast milk has been detected, suggesting that they may be involved in the regulation of growth in early infancy and could influence the programming of energy balance later in life. This paper focuses on hormones present in breast milk and their role in glucose homeostasis.